Tinjauan Penelusuran Banjir (flood routing) Krueng Peudada Kabupaten Bireuen Dalam Upaya Mereduksi Puncak Banjir Tahunan - Intan Purnama Sari; Meliyana Meliyana; Muhammad Ridha (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Reservoirs is an alternative to overcome flood problem that occurs due to Krueng Peudada flood discharge. The Peudada Reservoir has cacthmen area of 426.54 km2 and the length of the main river is 44.38 km.The objective of this study to analyze the outflow hydrograph (peak flood discharge that exits through the Peudada Reservoir spillway), and the maximum capacity of the river downstream of the Peudada Reservoir.Analysis of flood discharge using Hydrograph Unit Synthetic Nakayasu and Hydrograph Unit Synthetic SCS. Flood rooting analysis through reservoirs using level pool routing method. The results of this study show that the Peudada Reservoir can reduce flood discharge by ± 59.66%. Spillway capacity is 3148.44 m3 / sec, greater than flood discharge of 1000 years return period of 1245.86 m3 / sec, while the river's capacity was only 539.60 m3 / sec. Some alternavtive for food controlling that can be taken are the construction of flood ways, increase river flow capacity and in case of flood discharge, there are sufficient time intervals to evacuate residents to a safe place.